Gravity Probe B data analysis: I. Coordinate frames and analysis models. (17th November 2015) - Silbergleit, A S; Keiser, G M; Turneaure, J P; Conklin, J W; Everitt, C W F; Heifetz, M I; Holmes, T; P W Worden Jr,
Abstract: Gravity Probe B (GP-B) was a cryogenic, space-based experiment testing the geodetic and frame-dragging predictions of Einstein's theory of general relativity (GR) by means of gyroscopes in Earth orbit. This first of three data analysis papers reviews the GR predictions and details the models that provide the framework for the relativity analysis. In the second paper we describe the flight data and their preprocessing. The third paper covers the algorithms and software tools that fit the preprocessed flight data to the models to give the experimental results published in Everitt et al (2011 Phys. Rev. Lett. 106 221101–4 ).